WAVE VELOCITY MODELING ON SHALE USING LABORATORY MEASUREMENT AND GASSMANN - Retno Anggraini Ekawati, Dian
Shale is a clastic sedimentary rock consisting of silt and clay components. Shale gas is natural gas formed and trapped in the shale formation. In the exploration and exploitation of shale gas, it is necessary to predict the porosity and gas saturation of shale rocks indirectly using indirect measurement through seismic waves. Therefore, it is necessary to study the effects of seismic waves (???????? dan ???????? ) in various pressure, elastic rock parameters, and porosity using both seismic rock physics laboratory tests and numerical modeling. In this research, laboratory measurements were conducted using Seiscore equipment and also numerical modeling using Gassmann's equation and Hertz-Mindlin. The result of this research showed the feasibility of the Gassmann's equation and Hertz-Mindlin for modeling seismic wave and their correlations can be predicted reasonably well and closely resembled the results of laboratory measurements. The Gassmann approach has an average error of 0.09% and 0.08% for P and S wave velocity, respectively, while the Hertz-Mindlin approach has an error of 0.9% and 19.94%. Both the Gassmann and Hertz-Mindlin to determining wave velocity have characteristics that can be impacted by variations in porosity, bulk modulus, and shear modulus of rock. The velocity results of P and S waves increases logarithmically when pressure is applied to shale rock, which is strongly affected by the porosity factor and the elastic properties of the rock. The porosity of shale rocks ranges between 1-18% using the Gassmann's equation and 4.8-11% using the HertzMindlin approach, which decreases with increased pressure on the rock.